2017
DOI: 10.1097/igc.0000000000001026
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Gynecological Cancers in Turkey: Toward Europe or Asia?

Abstract: This is the first national cancer registry report to be published for gynecological cancers by the Turkish Governmental Department. As a result, Turkish gynecological cancer epidemiological data were consistent with the data obtained from European and developed countries rather than Asian countries, except for cervical cancer incidence, which is extremely low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 14 publications
2
24
0
2
Order By: Relevance
“…Gynecological tumor is an important cause of death globally and accounted for approximately 10.35% of cancer-related deaths. [ 37 ] Among the various risk factors of female reproductive tumors, vitamin D could not be ignored. Previously, there were studies stating that vitamin D deficiency could increase the risk of some specific gynecological tumors, such as ovarian cancer, uterine fibroids, and endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Gynecological tumor is an important cause of death globally and accounted for approximately 10.35% of cancer-related deaths. [ 37 ] Among the various risk factors of female reproductive tumors, vitamin D could not be ignored. Previously, there were studies stating that vitamin D deficiency could increase the risk of some specific gynecological tumors, such as ovarian cancer, uterine fibroids, and endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The ASR of endometrial cancer, from a population-based study in the Songkhla Province, was lower than in Korea [20] Taiwan [21], Romania [22], Turkey [23], Croatia [24], and Netherland [25], which were 7.0, 7.5, 8.2, 10.4, 11.4, and 20.1 per 100,000 women-years, respectively, but higher than in; Tunisia [26] and mainland China [27], which were 3.1 and 5.0 per 100,000 women-years, respectively. The annual percentage change of uterine cancer within the Songkhla Province was; 4.6% per year, which was lower than Tunisia [26] (7.1% per year), but higher than Turkey [23] and the Netherlands [25] (2.4% and 3.4% per year, respectively). However, these studies reported incidence between 2003 and 2013, in this study we reported recently in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the incidence of leiomyosarcoma was calculated to be 0.08%, which is relatively lower than that reported in other studies. There are only a limited number of studies in Turkey regarding the incidence of occult leiomyosarcoma; however, a previous study in Turkey has reported an annual leiomyosarcoma incidence of 0.26% [22].…”
Section: Discussionmentioning
confidence: 99%